Câmbio, juros e o movimento de reservas: Faz sentido o uso de um "quebra-molas"? - Dionísio Dias Carneiro; Thomas Yen Hon Wu (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2002)
– We examine the relationship between international reserves variation and the exchange rate and interest rate movements for the past years of the Brazilian economy. The empirical evidence obtained for the international reserves variation captures the distinction between the two exchange rate regimes after stabilization and that the international reserves movements has been affected by the movements of the interest rate and of the exchange rate (the observed exchange rate as a proxy of the expected exchange rate). Furthermore, the results suggest a reason for the Central Bank conservative behavior in keeping the interest rate high in order to avoid excessive movements of the international reserves.
Keywords: 330; Währungsreserven; Wechselkurs; Zins; Brasilien